Effect of Operating Room Guidelines on Rates of Surgical Site Infections in Patients Undergoing Spinal Procedures: A Single Institution Experience. (16th November 2020) - Warren, Kwanza T; Liu, Linxi; Schmidt, Tyler; Kimmell, Kristopher T; Li, Yan M; McMorrow, Christie M; Girgis, Pierre S; Zeidman, Seth M; Vates, G. Edward; Walter, Kevin A
Abstract: INTRODUCTION: Surgical Site Infections (SSIs) for patients undergoing spinal surgery can result in significant health and economic consequences. In 2015, the Association of periOperative Registered Nurses (AORN) published guidelines regarding operating room attire that were quickly adopted by our institution and national accrediting bodies. METHODS: All adult patients undergoing a spinal operation from 2013–2018 at our institution were identified. Patients were categorized based on the timing of their procedure with institutional operating room policies. Data from the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) were also collected for comparison. RESULTS: A total of 4, 849 patients were included in this study. The SSI rate was 1.26% prior to the policy change and, 1.44% afterwards ( P = .7500). Patients with SSI were found to have longer operative time ( P < .0001) higher ASA classification ( P = .0003), and different surgery location (0.0012) compared to patients without SSI. Data from the ACS-NSQIP database included 176, 821 patients and yielded similar results. CONCLUSION: There is no evidence that implementation of the stringent AORN guidelines results in a reduction of SSI rates for patients undergoing spine surgery.